ACS in children with sickle cell anaemia in Uganda: prevalence, presentation and aetiology. (20th August 2018) - Ochaya, Odong; Hume, Heather; Bugeza, Sam; Bwanga, Freddie; Byanyima, Rosemary; Kisembo, Harriet; Tumwine, James K.
Summary: ACS (ACS) is a serious complication of sickle cell anaemia (SCA). We set out to describe the burden, presentation and organisms associated with ACS amongst children with SCA attending Mulago Hospital, Kampala, Uganda. In a cross‐sectional study, 256 children with SCA and fever attending Mulago Hospital were recruited. Chest X‐rays, blood cultures, complete blood count and sputum induction were performed. Sputum samples were investigated by Ziehl‐Nielsen staining, culture and DNA polymerase chain reaction (PCR) for Chlamydia pneumoniae . Of the 256 children, 22·7% had ACS. Clinical and laboratory findings were not significantly different between children with ACS and those without, besides cough and abnormal signs on auscultation. Among the 83 sputum cultures Streptococcus pneumoniae (12%) and Moraxella spp (8%), were the commonest. Of the 59 sputa examined with DNA PCR, 59·3% were positive for Chlamydia pneumoniae . Mycobacterium tuberculosis was isolated in 6/83 sputa. These results show that one in 5 SCA febrile children had ACS. There were no clinical and laboratory characteristics of ACS, but cough and abnormalities on auscultation were associated with ACS. The high prevalence of Chlamydia pneumoniae in children with ACS in this setting warrants the addition of macrolides to treatment, and M. tuberculosis should be differential in sub‐Saharan children with ACS.